The Effect of Detention Pond’s Outlet Design to the Peak Discharge of a Watershed - Ab Rashid, Mohamad Azwan (Universiti Teknologi PETRONAS, 2013)
Flood occurs when the water discharge of a watershed exceed the drain capacity. One of the solutions to avoid flood when this occurs is by having a detention pond to control the amount of water discharge below the discharge capacity of the drain. This research project is to explore further on the effect of detention pond built in terms of its outlet design base on simple outlet structures frequently used by JPS